Abdominal mature cystic teratoma: Imaging findings and surgical specimen : Abdominal mature cystic teratoma: Imaging findings and surgical specimen (Revista Médica de Trujillo, 2023)
A 3-month-old female patient with a history of inguinal hernia was admitted to hospital due to febrile syndrome. On physical examination with abdominal distension, during her hospital stay MRI of the abdomen and pelvis was performed with gadolinium contrast (A) with findings of intraperitoneal mass in the left flank, mesogastrium and epigastrium, with cystic appearance, thin-walled, with solid component inside, with small hyperintense areas that show signal suppression in sequences with fat saturation, which may correspond to lipomatous component, with mass effect, associating displacement of the thin intestinal loops and the colon, without infiltration of adjacent organs, to consider the possibility of mature cystic teratoma, with approximate dimensions of 10.9 x 8.7 x 10.9 cm (L x AP x T). Subsequently, a histopathological sample of the surgical specimen (B) compatible with mature cystic teratoma was taken to the pediatric surgery department for resection.